A study to compare the internal fitness and marginal gap between single crowns and crowns within three-unite bridge of zirconia substructure fabricated by CAD-CAM system. (An In vitro study) - Auday M. Asady; Haitham J Al azzawi (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Purpose: the aim of this in vitro study was to compare the marginal gap and internal fitness between single crowns and the crowns within three-unit bridges of zirconium fabricated by CAD-CAM system. Materials and methods: A standard model from ivoclar company was used as a pattern to simulate three-units bridge (upper first molar and upper first premolar) as abutments used to fabricate stone models, eight single crowns for premolar and eight of three units bridges. Crowns and bridges fabricated by CAD-CAM system were cemented on their respective stone models then sectioned at the mid-point buccolingaully and misiodistaly and examined under stereomicroscope. Result: the marginal gap in premolar crowns and premolar within bridge were within the acceptable value 120µm, one -way ANOVA showed that there was significant differences in the internal gaps among the areas. Independent t- Test showed there was significant differences between the premolar crowns and premolar crowns within bridges in marginal opening and cusp tip (lingually and distally) Conclusion: the marginal and internal gaps were in the bridge higher than those in the crowns. The areas of sloped surfaces such as chamfer area, occlusal area and cusp tip had high gap values in comparison with areas of flat surfaces such as axial wall and when the surface area of abutment increased, the marginal and internal gaps of abutment was increase.